Hubungan Stress Dan Pola Makan Dengan Kejadian Hipertensi Di Rumah Sakit Bakti Timah Karimun - Pamela Afianti Pangaribuan (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Hypertension is the medical definition of high blood pressure. This condition can cause various complications and even death. There are several risk factors that can cause hypertension such as stress levels and poor dietary habits. Objective: to determine the relationship between stress and diet with the incidence of hypertension at the bakti tin hospital in karimun. Methods: This study used a quantitative design with a cross-sectional approach in 92 hypertensive patients using Chi-Square analysis techniques. Results: It is known that respondents who have mild stress are 34 patients (37%) more than patients with moderate and severe stress. Patients who have a good diet as many as 57 patients (62%) are greater than patients who have a poor diet. In this study, patients who had normal blood pressure were 31 patients (33.%), while first-degree hypertension was 27 patients (29.3%), second-degree hypertension was 32 patients (34.8%), third-degree hypertension was 2 patients (2.2%). The results of the analysis show that stress and diet have a relationship with the incidence of hypertension with p value (stress = 0.015, diet = 0.001). Conclusion: there is a relationship between stress and diet with the incidence of hypertension in the bakti tin hospital in karimun. Suggestion: In this case the nurse should be able to provide education to patients so that they can control their minds to avoid stress and regulate their diet to avoid the risk of increasing blood pressure.